Analisis Campur Kode Dalam Channel YouTube The Leonardo’s - Aisyah Eka Pratiwi; Novika Ningrum; Rosyiana Mutmainnah; Yumna Zubaidah Ufairah; Shafirra Fitrianoor; Mustofa Mustofa (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This research departs from the people who often mix one language with another in saying sentences. This study aims to analyze the use of code mixing. The phenomenon of code mixing or mixing of language codes can be understood as the use of language variations in one communication discourse. The method used is qualitative with a content analysis approach to analyze code mixing. Content analysis is observation by watching and listening to YouTube content and then recording speech using mixed code. The data collection used is observation by watching and listening to YouTube content and then recording speech using a mixed code. The results of this study reveal that several things that affect code mixing can be caused by several factors, namely the existence of language interactions between speakers and interlocutors, talking about a topic by choosing diction using code mixing.